Aspectos tributários das entidades fechadas de previdência complementar - Mazará, Lucia Helena Santana D'Angelo (2007)
This study has the objective to discuss about the Legal norms which regulates the Complementary Social Security Closed Entities EFPC, casting the tribute types and treating the incidence of each one of them over the entities and/or the benefits and recovery payments, according to each case. The study adopts as systemic base line the lessons of Professor Paulo de Barros Carvalho regarding the tributary incidence matrix-rule, in order to catch a glimpse of the correct interpretation of the tributes. The outcome of the work is the tributes compile: Income Taxation, Social Contribution over the Net Profit CSLL, PIS/PASEP, Cofins & CPMF treated individually under the Complementary Social Security Closed Entities point of view. Nevertheless, brief considerations regarding the Social Burden and its consequences to the entities are weaved in the end